Interplay between quantitative trait loci for stem strength and agronomic traits in a wheat doubled-haploid population - J. Allan Feurtado; Letitia M. Da Ros; Shola H. Kareem; Breenah Mulligan; Daiqing Huang; Lanette Ehman; Parul Jain; Leah K. Flatman; Hanna Hovland; Jeff Hovland; Brett Beckie; Richard D. Cuthbert; et al. (Field Crops Research, 2025)

Breeding oat for resistance to the crown rust pathogen Puccinia coronata f. sp. avenae: achievements and prospects - R. F. Park; W. H. P. Boshoff; A. L. Cabral; J. Chong; J. A. Martinelli; M. S. McMullen; J. W. Mitchell Fetch; E. Paczos-Grzęda; E. Prats; J. Roake; S. Sowa; L. Ziems; et al. (Theoretical and Applied Genetics, 2022)
Crown rust, caused by Puccinia coronata f. sp. avenae ( Pca ), is a significant impediment to global oat production. Some 98 alleles at 92 loci conferring resistance to Pca in Avena have been designated; however, allelic relationships and chromosomal locations of many of these are unknown. Long-term monitoring of Pca in Australia, North America and elsewhere has shown that it is highly variable even in the absence of sexual recombination, likely due to large pathogen populations that cycle between wild oat communities and oat crops. Efforts to develop cultivars with genetic resistance to Pca began in the 1950s. Based almost solely on all all-stage resistance, this has had temporary benefits but very limited success. The inability to eradicate wild oats, and their common occurrence in many oat growing regions, means that future strategies to control Pca must be based on the assumption of a large and variable prevailing pathogen population with high evolutionary potential, even if cultivars with durable resistance are deployed and grown widely. The presence of minor gene, additive APR to Pca in hexaploid oat germplasm opens the possibility of pyramiding several such genes to give high levels of resistance. The recent availability of reference genomes for diploid and hexaploid oat will undoubtedly accelerate efforts to discover, characterise and develop high throughput diagnostic markers to introgress and pyramid resistance to Pca in high yielding adapted oat germplasm.

Mapping of the stem rust resistance gene Pg13 in cultivated oat - Aida Z. Kebede; Belayneh Admassu-Yimer; Wubishet A. Bekele; Tyler Gordon; J. Michael Bonman; Ebrahiem Babiker; Yue Jin; Sam Gale; Charlene P. Wight; Nicholas A. Tinker; Jim G. Menzies; Aaron D. Beattie; et al. (Theoretical and Applied Genetics, 2020)

Progress in assessing the impact of Fusarium head blight on oat in western Canada and screening of avena germplasm for resistance - A. Tekauz; J. Mitchell Fetch; B. Rossnagel; M. Savard (Cereal Research Communications, 2008)

DNA markers for Fusarium head blight resistance QTLs in two wheat populations - J. A. Anderson; R. W. Stack; S. Liu; B. L. Waldron; A. D. Fjeld; C. Coyne; B. Moreno-Sevilla; J. Mitchell Fetch; Q. J. Song; P. B. Cregan; R. C. Frohberg (Theoretical and Applied Genetics, 2001)